Understanding the differences in cultivated land protection behaviors between smallholders and professional farmers in Hainan Province, China - Xu, Tao; Chen, Haojie; Ji, Yifan; Qiao, Dan; Wang, Fang (Frontiers in Sustainable Food Systems, 2023)
It is of practical significance to explore the differences and causes of cultivated land protection behaviors (CLPB) between smallholders and professional farmers for formulating targeted protection policies and alleviating the pressure of agricultural development on environmental protection. Based on 422 mango farmers’ survey data in Hainan Province, this paper explored the internal characteristics between smallholders and professional farmers, and used the Fairlie decomposition method to compare and analyze the sources of differences in farmers' CLPB. The results showed that: (1) the CLPB of smallholders and professional farmers differ significantly; (2) the sources of differences in CLPB between smallholders and professional farmers are different, including differences in internal characteristics and differences in external characteristics; (3) differences in internal characteristics are the main reason for differences in CLPB, planting years, annual income and planting scale were the main reasons for the differences in external characteristics. It is suggested that differential protection policies should be designed for smallholders and professional farmers, such as guiding smallholders to carry out large-scale operations and improve their organizational level, encouraging and guiding professional farmers to sign long-term contracts to stabilize the land tenure, formulating subsidy policies and improving the extension service system for cultivated land protection.